Analysis of the impact of training on the performance of Small and Medium-sized enterprises in Northwest Mexico, by applying the Structural Equations Statistical Technique (SEM-PLS) - Vásquez-Torres María Del Carmen; Salazar Arturo Tavizón; López José Guadalupe Flores (Management, 2021)
Small and medium enterprises (SMEs) are fundamental to the economy of all countries, representing the majority, with a considerable contribution to GDP, as well as generating jobs; for this reason, it must seek to remain in the market. The objective is to analyze the impact of training on the organizational performance of SMEs in northwestern Mexico, applying the statistical technique of structural equations model (SEM-PLS); the research was conducted to 195, considering the commercial, industrial and services, is a quantitative study, descriptive, correlational, causal, using the statistical technique of structural equations with the SMART PLS 3.3.2 software, and not experimental cross-sectional. The alternative hypothesis is accepted, since training has an effect on the organizational performance of SMEs in northwestern Mexico. It is highly significant because there is very strong evidence of the causality of the mediating variable training on the organizational performance of SMEs with 99.9% reliability. Training has the greatest effect on organizational performance because each unit that increases training will have an effect of +0.453, being the variable with the greatest cause-effect impact on organizational performance in SMEs in northwestern Mexico.